ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIFITAS PADA USAHA INDUSTRI RUMAH TANGGA KERUPUK UDANG DI DESA KAMPUNG LAUT KECAMATAN KUALA JAMBI - Rusmah Khairunnisa; Sissah; Mellya Embun Baining (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to determine the factors that influence productivity in the home industry of money crackers in Kampung Laut village, Kuala Jambi district. In this research, researchers used quantitative methods, while the sampling technique determined by researchers used saturated samples. Data collection used observation, questionnaires and interviews. The sample taken in this research was 30 workers. The data analysis methods used are validity test, reliability test, classical assumption test, normality test, heteroscedasticity test, multicollinearity test, f test, t test, multiple regression test, and coefficient of determination (adjusted r2), contribution dominance test. The results of the research show that: (1) it was found that simultaneously there is a significant influence of the variables education, training, motivation and rewards on the productivity of the shrimp cracker business in Kampung Laut village. Meanwhile, education and training variables do not have a significant effect on the productivity of the shrimp cracker business in Kampung Laut village. (2) it was found that partially the direction of the influence of the education and reward variables had a positive effect (moving in the same direction) on the productivity of the shrimp cracker business in Kampung Laut village. Meanwhile, the education and training variables have a negative influence (in the opposite direction) on the productivity of the shrimp cracker business in Kampung Laut village. (3) motivation variables contribute more dominantly than education, training and rewards to the productivity of the shrimp cracker business in Kampung Laut village. This provides direct and indirect information that shrimp cracker business actors in Kampung Laut village must increase the productivity of their business in order to obtain profits that are in line with what they expect or can increase their income.